The Interplay of Art, Occultism and Emancipation: Subversive Female Perspectives in Tyra Kleen's Life and Work at the Turn of the Twentieth Century - Bruchmüller, Birte (Approaching religion, 2025)
In the early 1900s, the Swedish noblewoman Tyra Kleen (1874-1951) was a highly productive artist, author, suffragette and occult seeker. Although Kleen’s esoteric and feminist interests have to a limited extent been considered in previous research, these aspects have not received sufficient attention, either in relation to her art/writing or as relevant interests in their own right. Research on Tyra Kleen, in general, is scarce, especially on her identity beyond an artist and author. Therefore, this study focuses on the interplay between Kleen's engagement in the women's suffrage movement and occultism, and her creative output around 1900. By examining how these overlapping spheres of interest informed one another, this study aims to situate and comprehend Kleen more fully within her contemporary cultural, social and political context. It highlights the spiritual, political and social conflation of Kleen's diverse emancipatory roles, and examines, among other factors, the importance of her companionship with Ellen Key in this context.